Electrostatic Problem for Toroid Surfaces: Analytical Regularization - Tuchkin, Yury A.; Panin, Sergey B.; Efe, Ibrahim; Dikmen, Fatih; Unal, Ilhami; Poyedinchuk, Anatoly Ye (IEEE, 2021)
The electrostatic problem described by the Laplace equation with Dirichlet boundary condition was rigorously and efficiently solved for closed and open arbitrarily shaped isolated toroid surface of revolution. Application of Orthogonal Polynomial Method and Analytical Regularization Method allowed the problem to be reduced to a well-conditioned infinite system of linear algebraic equations of the second kind. It possesses robust numerical solution with, in principle, any desired accuracy.
International Symposium of the Applied-Computational-Electromagnetics-Society (ACES) -- AUG 01-05, 2021 -- ELECTR NETWORK
Keywords: analytical regularization; closed and open toroid surfaces; potential problem